Assistance in Making Dynamic Electricity KITs Based on Scientific Argumentation Skills for Physics Teachers in Sidoarjo Senior High School - Utama Alan Deta; Muhammad Nurul Fahmi; Alfi Nurlailiyah; Ria Rusmawati; Mita Anggaryani; Budi Jatmiko (Universitas Lambung Mangkurat, 2023)
Physics learning cannot be separated from studying abstract concepts and practical activities to help students understand concepts in real terms. In the learning process, practical tools are needed to made easily and used in learning. The limited equipment in the laboratory is one of the obstacles to the lack of optimal learning activities, especially in practical activities. Therefore, teachers are required to be more creative and innovative in utilizing the tools around them so they can be used as practical tools. Dynamic electricity is also seen as an abstract concept requiring a practicum so that students can understand the concept real and meaningfully. Then, the other obstacle is scientific argumentation skills that still need to be better trained or not contained in the learning materials. It makes students' skills in scientific argumentation still lacking. The solution is: Synergize with the Physics Senior High School Teachers in Sidoarjo. They are trained through training to make physics practicum tools. Thus, the training participants can make these practical tools, can arrange student worksheets according to these tools and based on scientific argumentation skills. They can apply them in learning at their school. The result of this training is that the response of the Physics Senior high school teachers to the materials and demonstrations is very enthusiastic and interesting. This is evidenced by the average response questionnaire results of 3.44 with the maximum value of the questionnaire being 4. The maximum value obtained based on the response questionnaire is 3.66 and the lowest is 3.28.